Measuring Transcription Rate Changes via Time-Course 4-Thiouridine Pulse-Labelling Improves Transcriptional Target Identification. Issue 21 (23rd October 2015) - Schwarzl, Thomas; Higgins, Desmond G.; Kolch, Walter; Duffy, David J.
Abstract: Identifying changes in the transcriptional regulation of target genes from high-throughput studies is important for unravelling molecular mechanisms controlled by a given perturbation. When measuring global transcript levels only, the effect of the perturbation [e.g., transcription factor (TF) overexpression or drug treatment] on its target genes is often obscured by delayed feedback and secondary effects until the changes are fully propagated. As a proof of principle, we show that selective measuring of transcripts that are only synthesised after a perturbation [4-thiouridine (4sU) sequencing (4sU-seq)] is a more sensitive method to identify targets and time-dependent transcriptional responses than global transcript profiling. By metabolically labelling RNA in a time-course setup, we could vastly increase the sensitivity of MYCN target gene detection compared to traditional RNA sequencing. The validity of targets identified by 4sU-seq was demonstrated using chromatin immunoprecipitation sequencing and neuroblastoma microarray tumour data. Here, we describe the methodology, both molecular biology and computational aspects, required to successfully apply this 4sU-seq approach. Graphical abstract: Highlights: Discovering TF targets using a time-course experimental design. Metabolic pulse-labelling combined with high-throughput time-course sequencing. Improved TF target discovery compared to traditional RNA sequencing.